MANAJEMEN RISIKO KEUANGAN BANK PADA KASUS PENEMPATAN DANA NASABAH DI MAYBANK - Syahrul Ramadhan Thayib Thayib; Irma Nuryani Inaku (Manajemen Keuangan Syariah, 2022)
Riskmanagement is a series of procedures or methods  used to identify, measure, monitor and control risks arising from the bank's business activities. The implementation of risk management will provide better benefits to banks. For banks, the implementation of this risk management can increase shareholder value, as well as provide an overview to bank managers about the possibility of losses on the part of the bank in the future. Related to a problem or case that occurs in the banking world, one of which is a reporting case of losing money worth 20 billion rupiah which was lost because it was stored in a bank. This case was reported by a customer of PT Bank Maybank Indonesia Tbk (Maybank Indonesia) named Winda Lunardi (Winda Earl) an esports athlete who claimed to have lost 20 billion rupiah worth of money in his personal Maybank account and his mother named Floletta.  In this study obtained the results of research from observations and documentation related to forms of risk management and factors that cause fraud at Maybank Cipulir Jakarta, the types of risks arising from this case are Operational Risk, Compliance Risk, Legal Risk, and Reputation Risk.  The impact caused when there are various kinds of risks, namely Loss and Loss of Customer Trust.